Correlation between Levels of 2, 5-Hexanedione and Pyrrole Adducts in Tissues of Rats Exposure to n-Hexane for 5-Days - Yin, Hongyin; Guo, Ying; Zeng, Tao; Zhao, Xiulan; Xie, Keqin (PLOS ONE, 2013)
BackgroundThe formation of pyrrole adducts might be responsible for peripheral nerve injury caused by n-hexane. The internal dose of pyrrole adducts would supply more information for the neurotoxicity of n-hexane. The current study was designed to investigate the tissue distributions of 2, 5-hexanedione (2,5-HD) and pyrrole adducts in rats exposed to n-hexane, and analyze the correlation between pyrrole adducts and 2,5-HD in tissues. MethodsMale Wistar rats were given daily dose of 500,1000, 2000, 4000 mg/kg bw n-hexane by gavage for 5 days. The rats were sacrificed 24 hours after the last administration. The levels of 2, 5-hexanedione and pyrrole adducts in tissues were measured by gas chromatography and Ehrlich’s reagent, respectively. The correlations between 2, 5-hexanedione and pyrrole adducts were analyzed by linear regression ResultsDose-dependent effects were observed between the dosage of n-hexane and 2, 5-hexanedione, and pyrrole adducts in tissues. The highest level of 2, 5-hexanedione was found in urine and the lowest in sciatic nerve, while the highest level of pyrrole adducts was seen in liver and the lowest in serum. There were significant correlations among the free 2, 5-hexanedione, total 2, 5-hexanedione and pyrrole adducts within the same tissues. Pyrrole adducts in serum showed the most significant correlation with free 2, 5-hexanedione or pyrrole adducts in tissues. ConclusionThe findings suggested that pyrrole adducts in serum might be a better indicator for the internal dose of free 2, 5-hexanedione and pyrrole adducts in tissues.